2006
DOI: 10.1074/jbc.m603767200
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Roles of Sp1 and Epigenetic Modifications in the Regulation of the CLDN4 Promoter in Ovarian Cancer Cells

Abstract: Claudins form a large family of tight junction proteins that have essential roles in the control of paracellular ion flux and the maintenance of cell polarity. Many studies have shown that several claudin family members are abnormally expressed in various cancers. In particular, CLDN4 (encoding claudin-4) is overexpressed in ovarian cancer. However, although CLDN4 overexpression is well established, the mechanisms responsible for this abnormal regulation remain unknown. In the present study, we delineate a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
104
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(116 citation statements)
references
References 34 publications
11
104
1
Order By: Relevance
“…Therefore, disruption of the tight junction can cause the loss of cell polarity, resulting in an abnormal infl ux of growth factors, which could provide autocrine and paracrine stimulation to tumorigenic epithelial cells [5]. However, the exact roles of tight-junction-associated proteins in gastric cancer remain unclear [18].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, disruption of the tight junction can cause the loss of cell polarity, resulting in an abnormal infl ux of growth factors, which could provide autocrine and paracrine stimulation to tumorigenic epithelial cells [5]. However, the exact roles of tight-junction-associated proteins in gastric cancer remain unclear [18].…”
Section: Discussionmentioning
confidence: 99%
“…30 Similarly, alteration of claudin-4 expression in bladder carcinoma was found to be associated with DNA methylation, 21 and epigenetic modifications including histone acetylation and DNA demethylation have been reported to be involved in the increase of CLDN4 expression in ovarian cancer cells. 32,33 Interestingly, our recent study 33 revealed that claudin-4 overexpression during ovarian tumorigenesis is associated with loss of repressive histone methylations, suggesting that epigenetic derepression also contributes to tumorigenesis by activation of cancer-promoting genes. However, the molecular mechanism responsible for the alteration of claudin-4 expression during gastric tumorigenesis is unclear.…”
mentioning
confidence: 99%
“…Accumulating evidence supports the role of such epigenetic silencing mechanisms as methylation and inactive histone modifications in the transcriptional inactivation of tumor suppressor genes during cancer developmental processes (Ballestar and Esteller, 2008;Baylin and Jones, 2007;Robertson, 2005). In contrast, tumor progression may involve the epigenetic activation of oncogene-like genes, as evidenced by the upregulation of galectin-7, CLDN4, uPA, and MMP-2 genes in several cancer cells via DNA hypomethylation in their promoter regions (Chernov et al, 2009;Demers et al, 2009;Guo et al, 2002;Honda et al, 2006;Pakneshan et al, 2004;Shvachko, 2009). This epigenetic activation involves the reversal of inactive epigenetic marks including histone deacetylation by histone acetylation and DNA methylation by DNA hypomethylation.…”
Section: Discussionmentioning
confidence: 95%
“…Methylation of CpG dinucleotides located within DNA recognition elements may interfere with the binding of transcription factors, which inhibits transcription (Siegfried et al, 1999). Methylated CpG dinucleotides interfere with SP1 binding and further the reduced binding of Sp1 may be involved in suppression of transcriptional activity of the genes such as AQP5, and CLDN4 (Clark et al, 1997;Honda et al, 2006;Kudo, 1998;Mancini et al, 1999;Motegi et al, 2005;Zhu et al, 2003). In agreement with these findings, we observed that the normal breast epithelial cells MCF-10A had a heavily methylated potential SP1-binding site, the ninth CG of the LIF promoter, while benign and carcinoma MCF10 variants did not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation